Strategi Fundraising Di Badan Amil Zakat Daerah (Bazda) Kota Bekasi - Humaini, Ayatulloh (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2013)
One of the major success factors of a Zakah Management Organization (Organisasi Pengelola Zakat/OPZ)—whether it is BAZIS or LAZIS—is its sincerity in carrying out fundraising. If OPZ is active, both in planning and fundraising strategy, the existence of OPZ will last long. Local Zakat Agency (Badan Amil Zakat Daerah/BAZDA) Bekasi is a one of OPZ that has been in progress and development, particularly in fundraising results. This success is inseparable from fundraising strategy that has been implemented by BAZDA Bekasi. The results of this research illustrated that in 2012 BAZDA Bekasi had arranged two strategies: First of all the core strategy, consisted of: zakat collection unit, special Ramadan events, charity boxes, and media campaign. Secondly, a specific strategy, included convenience donation, post-donation services, and programs of action.Keywords: strategi fundraising, BAZDA, strategi inti, dan strategi khusus.